Tremor and generalized mioclonus caused by meglumine antimoniate - Torres-Ramírez, Luis (2020)
Cutaneous Leishmaniasis is an endemic pathology in Peru, the first line treatment being pentavalent antimonials. Occasional antimonials as the side effect, neurological symptoms that can become incapacitating, so we must be strict in the dosage at the time of administration. We present the case of a 56-year-old male patient, who treated with Meglumina Antimoniate (Glucantime®), presented tremor, dysmetria, ataxia and generalized myoclonus that prevented him from walking